The importance of MICE services to the hotel industry and their value during the tourist low season. (20th April 2023) - Ashrapov, Djamshid; Patterson, Ian
This exploratory study provides an examination of the importance of MICE services to the hotel industry of the City of Bukhara in Uzbekistan. This paper uses a qualitative research design to interview eight senior hotel managers (four with MICE services; four without MICE services) to determine the importance of MICE tourism to their hotels as a means of increasing their operational revenue on a yearly basis. Very little has been written on MICE tourism in Uzbekistan as it is a new and emerging special interest tourism market. This study highlights some of the shortcomings in the provision of MICE services in Bukhara, and offers several recommendations to encourage hotels to increase their financial income, so as they are able to conduct their operational activities on an all-year round basis.